Design and implementation of tracking system based on image processing - Falah Fakhruldeen, Hassan; H. Al-Kharsan, Ibrahim (International Journal of Engineering and Technology, 2017)
A novel Variable Step Size Proportional algorithm (VSSP) has used for the sun-tracking system. The proposed algorithm does not require any feedback, and it can track the sun accurately even when there are obstacles around. Image processing techniques have been used to estimate the location of the sun, hence controlling the motors in each axis. A microcontroller board has been used to exchange data between the Matlab software, where the algorithm has written, and the peripherals. The system has offered an excellent ability to track the center of the sun in 15 iterations with 97% accuracy. The accuracy has been improved even more after 24 iterations to become 98.7%. Tracking the intensity of light is the most powerful prosperity of this algorithm that makes it able to track the sun even if it is out of the camera range. It does not require any complex processing or special sensors. The proportional controller is the base of this algorithm.Â Â Â